Whole genome survey analysis and microsatellite motif identification of Sebastiscus marmoratus. Issue 2 (24th February 2020) - Xu, Sheng-yong; Song, Na; Xiao, Shi-jun; Gao, Tian-xiang
Abstract: The marbled rockfish Sebastiscus marmoratus is an ecologically and economically important marine fish species distributed along the northwestern Pacific coast from Japan to the Philippines. Here, next-generation sequencing was used to generate a whole genome survey dataset to provide fundamental information of its genome and develop genome-wide microsatellite markers for S. marmoratus . The genome size of S. marmoratus was estimated as approximate 800 Mb by using K-mer analyses, and its heterozygosity ratio and repeat sequence ratio were 0.17% and 39.65%, respectively. The preliminary assembled genome was nearly 609 Mb with GC content of 41.3%, and the data were used to develop microsatellite markers. A total of 191, 592 microsatellite motifs were identified. The most frequent repeat motif was dinucleotide with a frequency of 76.10%, followed by 19.63% trinucleotide, 3.91% tetranucleotide, and 0.36% pentanucleotide motifs. The AC, GAG, and ATAG repeats were the most abundant motifs of dinucleotide, trinucleotide, and tetranucleotide motifs, respectively. In summary, a wide range of candidate microsatellite markers were identified and characterized in the present study using genome survey analysis. High-quality whole genome sequence based on the "Illumina+PacBio+Hi-C" strategy is warranted for further comparative genomics and evolutionary biology studies in this species.